Haemonchus contortus resistance to monepantel in sheep: Fecal egg count reduction tests and randomized controlled trials - Martins, Aline Carvalho [UNESP]; Bergamasco, Paula Luzia Formigoni [UNESP]; Felippelli, Gustavo [UNESP]; Tebaldi, José Hairton [UNESP]; Moraes, Marcela Figueredo Duarte [UNESP]; Testi, Alan Jonathan Pereira [UNESP]; Lapera, Ivan Moura [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP] (Universidade Estadual de Londrina, 2017)
Worm infections are a major cause of economic losses in sheep farming, and their control depends essentially on anthelmintic drugs. After decades without the discovery of new drug types, a new class of anthelmintics, called aminoacetonitrile derivatives, represented by monepantel, was released on the market. In order to evaluate a report of low efficacy of monepantel on a sheep farm in the municipality of Taiúva, state of São Paulo, Brazil, fecal egg count reduction and critical tests were performed on a Haemonchus contortus strain collected from this farm. To this end, ten animals were experimentally infected with 5000 H. contortus third-stage larvae, and these animals were divided into two groups, control and treated, according to the treatment with monepantel. The parameters evaluated were reduction in fecal egg counts on post-treatment days (PTD) 0, 2, 4, 7 and 14, and the therapeutic efficacy at the end of this period. Egg count reduction was observed starting on PTD 2, with a maximum reduction of 32.89% recorded on PTD 14. The critical test revealed 24.65% efficacy, indicating resistance to the active ingredient monepantel. The ineffectiveness of monepantel may be associated with the excessive use of the anthelmintic, which the farmer administered at intervals of less than one month, without technical guidance or a defined criterion. Given that the anthelmintic was used on this farm for less than one year, according to the farmer, it can be inferred that H. contortus develops resistance to monepantel in a few generations if the product is used incorrectly.
Keywords: Amino acetonitrile derivatives; Anthelmintic; Efficacy; Sheep